2004
DOI: 10.1016/j.str.2003.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of NarGH Reveals a Structural Classification of Mo-bisMGD Enzymes

Abstract: The structure of the catalytic and electron-transfer subunits (NarGH) of the integral membrane protein, respiratory nitrate reductase (Nar) has been determined to 2.0 A resolution revealing the molecular architecture of this Mo-bisMGD (molybdopterin-guanine-dinucleotide) containing enzyme which includes a previously undetected FeS cluster. Nar, together with the related enzyme formate dehydrogenase (Fdh-N), is a key enzyme in the generation of proton motive force across the membrane in Escherichia coli nitrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
279
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 195 publications
(282 citation statements)
references
References 52 publications
3
279
0
Order By: Relevance
“…The coordination of metal sites by side-chain carboxylates from aspartic and glutamic acid molecules has been the subject of several studies ( [36] and references therein). These studies showed that carboxylate groups present a high flexibility of coordination, as suggested by Jormakka et al [26].…”
Section: Membrane-bound Nitrate Reductasesmentioning
confidence: 66%
See 4 more Smart Citations
“…The coordination of metal sites by side-chain carboxylates from aspartic and glutamic acid molecules has been the subject of several studies ( [36] and references therein). These studies showed that carboxylate groups present a high flexibility of coordination, as suggested by Jormakka et al [26].…”
Section: Membrane-bound Nitrate Reductasesmentioning
confidence: 66%
“…In 2003 the whole complex NarGHI was reported, at a resolution of 1.9 Å [25], and in 2004 the heterodimer NarGH was solved to 2.0 Å resolution [26]. The heterotrimer Nar-GHI comprises a catalytic subunit (NarG, 140 kDa), a subunit containing four [4Fe-4S] centers (NarH, 58 kDa), and a membrane-bound heme b subunit (NarI, 20 kDa) (Fig.…”
Section: Membrane-bound Nitrate Reductasesmentioning
confidence: 99%
See 3 more Smart Citations